PENERAPAN MODEL PEMBELAJARAN (PBL) UNTUK MENINGKATKAN SIKAP SOSIAL DALAM PEMBELAJARAN IPS DI KELAS V - Awaludin Ikbal; Gigih Winandika; Dedi Setyawan; Sri Astuti Rezeki; Khaefa Azasis Anuar; A’im Matul A’malia; Sri Nur Eriwati; Cakrawala; Muflikhun Muflikhun; Dapi Aryadi (Arunika: Jurnal Pengabdian Masyarakat, 2026)
This research is motivated by the low level of social attitudes among fifth-grade elementary school students in Social Studies (IPS), characterized by a lack of cooperation, discipline, and responsibility, as well as low empathy toward others during discussions. To address this issue, the Problem-Based Learning (PBL) model was implemented using the Classroom Action Research (CAR) method, following the Kemmis and McTaggart design. This study, involving 28 subjects, was conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation techniques, questionnaires, interviews, and documentation. The findings showed a significant increase in students' social attitudes, rising from 58% during the pre-cycle to 72% in Cycle I, and reaching 86% in Cycle II. It can be concluded that the use of the PBL model is effective in optimizing students' social attitudes in Social Studies learning.